Consumer Protection Against Forced Withdrawal By Leasing Parties In Fiduciary Guarantee - Hernando Ariawan; Maryanto Maryanto (Law Development Journal, 2021)
The purpose of this research is to analyze consumer protection against forced withdrawals by leasing parties in fiduciary guarantees, constraints on consumer protection against forced withdrawals by leasing parties in fiduciary guarantees, and analyze consumer protection against forced withdrawals by leasing parties in fiduciary guarantees in the future. This study uses a sociological juridical approach, with analytical descriptive research methods. The data used are primary and secondary data which will be analyzed qualitatively. The research problem was analyzed using the theory of justice. The results of the study concluded that forced withdrawals were made to the debtor both physically and mentally due to the lack of heeding of the wishes of the leasing party. When the action that has a criminal threat is carried out by leasing, then there is no word for criminal abolition for them, except for certain reasons. The first party should use legal channels, namely through the courts in resolving the problem of default by the second party, so that there is permanent power in confiscation of goods against debtors in the event of bad credit. The use of Fiduciary Guarantees still has several obstacles, including: 1). Fiduciary Guarantee Registration. 2). Guaranteed vehicle withdrawals. 3). Elimination of Fiduciary Guarantee after the debt has been repaid. Consumer protection against forced withdrawals in fiduciary guarantees in the future should continue to be consistent with Act No. 8 of 1999 concerning Consumer Protection (UUPK). The enactment of this law provides hope for the people of Indonesia, to obtain protection for losses suffered by transactions of goods and services. UUPK guarantees legal certainty for consumers.